Hypoxia: help or cheat? - Sanchis-Gomar, F.; Gomez-Cabrera, M. C.; Martinez-Bello, V. E.; Domenech, E.; Nascimento, A. L.; Derbre, F.; Romagnoli, M.; Perez-Quilis, C.; Garcia-Gimenez, J. L.; Vina, J. (Archivos de medicina del deporte, 2008)
Intermittent hypoxia has been used as a method to improve the exercise performance. However recent publications reflect the antidoping authorities concern on the use of altitude training simulators systems. The use of recombinant human erythropoietin (rHuEPO) to enhance athletic performance is prohibited. The aim of our study was to determine whether intermittent hypoxic treatments could mask the detection of rHuEPO abuse. Our hypothesis is that after the hypoxic treatments there is an increase in endogenous levels of EPO and/ or reticulocytes and haemoglobin that may camouflage the rHuEPO abuse when determined using indirect (OFF-Hr Score) or direct methods (isoelectric focusing technique). Design and methods: Eight male young Wistar rats were treated, three times a week during two weeks, with 500 I.U. of rHuEPO-alpha. After the treatments the animals were randomly divided into two groups: one normoxic and one hypoxic. The normoxic group was maintained 24 hours at 21% O2 during 23 days. The hypoxic group was maintained 12 hours at 21% O2 and 12 hours at 12% O2 (~4500 m) for the same time period. Results: After the rHuEPO treatment, the hypoxic group of animals produced a faster recovery in the reticulocyte count, elevated levels of haemoglobin and haematocrit and a significant increase in the endogenous EPO levels when compared with the normoxic group of animals. Interpretation and conclusions: Intermittent hypoxic treatments after rHuEPO administration can be considered a system to avoid the detection of the rHuEPO by indirect and perhaps direct methods in an animal model.